"A Room Full of Chairs around His Bed": Being Present at the Death of a Loved One in Veterans Affairs Medical Centers. (May 2013) - Williams, Beverly Rosa; Bailey, F. Amos; Woodby, Lesa L.; Wittich, Angelina R.; Burgio, Kathryn L.
Historically, death took place at home where family held vigil around the dying patient. Today, family presence is an important feature of death and dying in hospital settings. We used hermeneutic phenomenology to explore experiences of being present at the hospital death of a loved one. We conducted in-depth, face-to-face interviews with 78 recently bereaved next-of-kin of veterans who died in 6 Veterans Affairs (VA) Medical Centers in the Southeast United States. Two major themes emerged: 1) " settling in, " characteristic of the experiences of wives and daughters in the initial phase of the patient's hospitalization; and 2) " gathering around, " characteristic of the experiences of a wider array of family members as the patient neared death. An in-depth understanding of experiences of next-of-kin present at the hospital death of a loved one can increase staff awareness of family's needs and empower staff to develop policies and procedures for supporting family members.